DEVELOPMENT OF PPKN LEARNING MEDIA BASED ON PICTURE STORIES TO IMPROVE CRITICAL THINKING SKILLS CLASS V STUDENTS OF SDIT PERMATA FIRDAUS - Lenni Hartati Manurung; Reh Bungana Beru Perangin-angin; Evi Eviyanti (Sensei International Journal of Education and Linguistic, 2021)
The study aims to describe the feasibility and effectiveness of civics learning media based on pictorial stories to improve students' critical thinking skills in Theme 8 Sub-theme 3 about the socio-cultural diversity of the society. This type of research is research and development. While the research design used is the research of Borg & Gall. The research subjects were made 1 teacher of class V and 25 students of class V, as well as 2 material experts and two media experts. Data was collected through questionnaires, tests, and interviews. Based on the results of material expert validation, an average score of 89.7% was obtained, while media experts obtained an average score of 87.9%, which was categorized as very feasible. Meanwhile, based on the results of the student response questionnaire, the average score obtained was 87.9%, which means the category is very good. In assessing students' abilities, the researchers conducted pre-test and post-test. From the results of the pre-test and post-test, it can be seen that there is an increase in students' critical thinking skills, namely the average score of 55% during the pre-test to 72.6% during the post-test. Based on the n-gain score assessment criteria, the effectiveness of picture story-based learning media obtained a value of 0.39, which means that it is in the range of 0.3 < g < 0.7 classified in the medium category.